PROPUESTA DE DISEÑO DE PLANTA Y MEJORA DE PROCESO EN LA LADRILLERA MEDIALUNA DE PIVIJAY, MAGDALENA (2023)
The purpose of this research work is to design and improve processes for the medialuna brick factory, solving the problems that said company presents, the tools that were used to solve the first objective were a factor analysis, Ishikawa diagram, process diagram, tool description, flow chart and taking time, these were the methods that were used to solve the first objective, Based on what was proposed, we can continue with the methods to solve the second, the The methods chosen to solve this purpose were a Guerchet method: this method was used to determine the ideal dimensions of a working point, the SLP method is a method that not only carries out the quantitative study of the dimensions of the plant, but also quantitatively evaluates the relationships between work areas. According to the above, it is proceeds to use the FlexSim software, in which the design of the current plan will be shown, and the proposed plant design, the economic viability and the distribution proposal by means of Cost-Benefit analysis.